2022
DOI: 10.3389/fchem.2022.1000910
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured 2D WS2@PANI nanohybrids for electrochemical energy storage

Abstract: 2D materials are interesting flat nanoplatforms for the implementation of different electrochemical processes, due to the high surface area and tunable electronic properties. 2D transition metal dichalcogenides (TMDs) can be produced through convenient top-down liquid-phase exfoliation (LPE) methods and present capacitive behaviour that can be exploited for energy storage applications. However, in their thermodynamically stable 2H crystalline phase, they present poor electrical conductivity, being this phase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The serious environmental pollution caused by fossil energy consumption has stimulated an unprecedented and urgent demand for eco-friendly energy conversion/storage devices. , Supercapacitors, as a green and sustainable energy storage system, have attracted extensive attention due to their outstanding electrochemical properties including excellent rate capability, high specific power, rapid charge–discharge rate, and long-cycle lifetime. , Since the electrode is one of the most essential parts of the supercapacitor, the development of high-performance electrode materials is particularly important. Among the various electrode materials, conductive polyaniline (PANI) has received considerable attention due to its exceptional properties such as low cost, facile preparation, good conductivity, and high theoretical specific capacitance. , However, the widespread application of PANI is significantly limited by the expansion and shrinkage during the charging/discharging process as these volume vibrations mostly lead to poor rate capability and cycle stability. , …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The serious environmental pollution caused by fossil energy consumption has stimulated an unprecedented and urgent demand for eco-friendly energy conversion/storage devices. , Supercapacitors, as a green and sustainable energy storage system, have attracted extensive attention due to their outstanding electrochemical properties including excellent rate capability, high specific power, rapid charge–discharge rate, and long-cycle lifetime. , Since the electrode is one of the most essential parts of the supercapacitor, the development of high-performance electrode materials is particularly important. Among the various electrode materials, conductive polyaniline (PANI) has received considerable attention due to its exceptional properties such as low cost, facile preparation, good conductivity, and high theoretical specific capacitance. , However, the widespread application of PANI is significantly limited by the expansion and shrinkage during the charging/discharging process as these volume vibrations mostly lead to poor rate capability and cycle stability. , …”
Section: Introductionmentioning
confidence: 99%
“…Through electropolymerization, Sayah et al prepared PANI-exfoliated graphene composite films (PANI-GR), which showed a significantly boosted supercapacitive performance of 305.6 F/g as compared with that of PANI of 176.3 F/g at 5 mV/s . Compared with graphene, tungsten disulfide (WS 2 ) nanosheets are much more attractive as additional pseudocapacitance can be provided through the Faradaic redox reaction and reversible intercalation/deintercalation of electrolyte ions. , Crisci et al reported that the incorporation of exfoliated WS 2 nanoflakes into the PANI matrix resulted in diploid capacitance of the WS 2 @PANI composite materials . Although there is a significant enhancement in supercapacitive performance, the 2D layered nanosheets tend to form aggregates, leading to the hindrance of ion transportation channels and degradation of long-term stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPE 1 is related to the C dl , while CPE 2 is associated with the Warburg coefficient, determined by the semi-infinite diffusion of the ions in the electrolyte. [42,43] The C dl was calculated using the equation reported by Bard and Faulkner. [44] From the fittings, all the samples exhibit slightly different values of R s , within 10% error.…”
Section: Resultsmentioning
confidence: 99%